Development of Methods of Optimization of Non-Tax Payments for Decrease in Expenses of the Company at Implementation of the Foreign Economic and Resource Activity. Optimization of Non-Tax Payments - BOBROVA, Anna Vladimirovna; STEPANOV, Evgeny Aleksandrovich; TETIN, Ilya Alekseevich (Journal of Advanced Research in Law and Economics; Vol 8 No 6 (2017): JARLE Volume VIII Issue 6(28) Fall 2017, 2017)
The subject of this research is non-tax payments in Russia: analogues of tax payments coming into the budget system, paid by legal entities or private individuals in addition to the tax burden based on environmental and resource payments. The purpose of this research is to develop a methodology for the optimization of non-tax payments based on their tax element-based structuring and recommendations for the implementation of non-tax payments in the Russian tax system. The main method used in the study is the method of system analysis; effectiveness assessment of tax payment-optimization activities, factor analysis, and the sampling method of normative legal acts are also used in the research. It is shown that non-tax payments must be optimized along with taxes to lower costs to the tax payer. A few problems were identified: problems of state regulation, problems connected with the legislative structure, and problems of optimization of tax payments by the payer. Above all, it is necessary to systematize non-tax payments by tax components to solve these problems. We establish the means of optimizing non-tax payments in accordance with the law, present tax evasion methods and responsibility for these actions, and suggest a number of measures to improve the system of non-tax payments in Russia. The results of this research can serve as the basis for legislative changes on non-tax payments and can be useful to legislators, regulators, non-tax payers, and those who study non-tax payments.